Answer:
x = -4, 4
Explanation:
Hi there!
![x^2-16=0](https://img.qammunity.org/2022/formulas/mathematics/college/ykyavlci9xn8g6fp4lu9e0tws6bu6k1ysq.png)
Rewrite 16:
![x^2-4^2=0](https://img.qammunity.org/2022/formulas/mathematics/college/r1elqx4a7qg5dikwyzzsq443r0su9b84km.png)
The difference of squares rule states that
. With this, apply the difference of squares to the equation:
![(x+4)(x-4)=0](https://img.qammunity.org/2022/formulas/mathematics/college/i9ptwu1p6ubrh6xmpz2jeuqzyj58ze7tb5.png)
The zero-product property states that if the product of two numbers is 0, then one of the numbers must be equal to zero. Set each term equal to 0 and find the solutions:
![x+4=0\\x=-4](https://img.qammunity.org/2022/formulas/mathematics/college/58262f9bz835vikblcn7gohircd2ztr4do.png)
![x-4=0\\x=4](https://img.qammunity.org/2022/formulas/mathematics/college/nmal6otwe2s2801xk416ft0i7galnfxpqc.png)
Therefore, the solutions are -4 and 4.
I hope this helps!